Entre objetos e performances: o Núcleo de Acervos da Escola de Música da UEMG no âmbito das relações entre música e museu - Aline Azevedo Costa (2020)
The dialog between areas of knowledge such as Musicology and Museology has shown a more technical perspective, in which music at the museum is handled in its sound dimension and interaction at spaces, exhibitions, educational actions or incorporating musical items as three-dimensional objects; music museum which discuss more frequently whether or not the usage of musical instruments at museum collections or a perspective related to performative practices of classical repertoires (music for museum or sound museum); and the context of museum of music as a storage space of collections, funds, archives or works in which musical museology promotes a specific yet partial reading and action, but does not promotes the combined reflection of this dialog, which is the object in this PhD dissertations thesis. In this panorama, the University of Minas Gerais` College of Music Archival Nucleus (Núcleo de Acervos da Escola de Música da Universidade do Estado de Minas Gerais, UEMG) – formally constituted in the year of 2007 and currently including ten musical archive from Minas Gerais (Brazil) – represents the target of this PhD dissertations thesis, in a case study approach intended to allow individual condition analysis of each fund and the holistic view of the Nucleus as a space in relation to selected museum function for this work: preservation, research and communication (MENSCH, 1992). To what extent can a musical archive or archival set act as a museum of music, regardless its formal designation or institutional as such? Therefore, this PhD dissertation thesis aims to reflect on and demonstrate how museological perspective – specifically in this case from the museum functions – dialogs with a musicological perspective, the material organization and the action planning in musical archives, contributing to a preliminary diagnosis. In addition to practical contributions, that is, as a proposal or model to be replicated in similar contexts, this research contributes to the knowledge field in which it formally inserts in the extent that it proposes a rapprochement not only between the concepts of music and museum, but likewise between knowledge fields that, in association, can bring a new panorama for musical archives, particularly with regards of the heritage communication in its material and immaterial aspects.